Complex geophysical research, geostatistical analysis and 3D modeling, with electrical and nuclear methods in Macanal and Chinavita, Boyacá, Colombia (2014)
The implementation of geophysical methods is very important in the realization of projects that permit avaluating us the geological formations geologically-geophysically and specifically units present lithologies in them. From now on the shows the survey area's geologycal frame in which himself i accomplish the methodology of fieldworks and results obtainded as from the implementation of electric method of radiometry. Just the same him self i accomplish an analysis geostatics of data of comparison among population by means of block diagrams of frequencies of physical measured parameters.